How do parents learn about raising children? (Journal of Parents and Teachers, 2025)
The article outlines a series of points regarding what parents learn during child-rearing, whether from the assigned doctor, their own experience, specialized magazines, books, older generations (i.e., their parents), local resources, or even specialists at school. Thanks to all of the above, a welcoming environment is created, with habits and guidelines, along with a united family and school.